Customer satisfaction of online shopping among employees of CMA CGM group Malaysia - Lee, Gin Gank (2018)
The purpose of this study is to investigate the relationship of perceived ease of use, service quality, website design and online security towards customer satisfaction of online shopping among employees of CMA CGM group Malaysia. 234 sets of questionnaires were distributed using systematic random sampling method. Out of 234 questionnaires only 224 set of questionnaires were returned. Questionnaire collected were usable with a response rate of 95.7%. The data collected were analysed using Statistical Package for Social Science (SPSS) version 23.0. Then, reliability analysis, descriptive analysis and inferential analysis were conducted. Through the reliability analysis, all variables used in this study are reliable with the value of each variable exceeds 0.6 as suggested by previous researcher. Besides, this study found that all the independent variables significantly relationship with customer satisfaction of online shopping among employees of CMA CGM group Malaysia (p < 0.01). Through the regression model (r = 0.653, r2 = 0.426), it indicated that 42.6% of customer satisfaction of online shopping among employees of CMA CGM group Malaysia was influenced to all the independent variables that are perceived ease of use, service quality, website design and online security. Customer satisfaction of online shopping among employees of CMA CGM group Malaysia is influenced mostly by online security. Next, the influence factors to customer satisfaction of online shopping among employees of CMA CGM group Malaysia were followed by perceived ease of use, service quality, website design, and lastly information quality. Future improvement this research, future research may conduct a qualitative research and added several appropriate variables.